Tribological and Thermal Characteristics of Organic Brake Pads Using Rubber Seed Shell and Rubber Fruit Shell as Filler - Brian Laksana Gemilang; Rina Lusiani; Iman Saefuloh; Sunardi Sunardi (ScopusID:57208466308) (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2022)
The Badan Pusat Statistik (BPS) data for 2021 shows that the total rubber production in Indonesia reached 2.877,90 tons. The high amount of rubber production will accompany many by-products, such as rubber seed shells and fruit shells. These materials have not been widely used for commercial purposes. This research will use rubber seed shells and fruit shells as brake pad filler. These materials are expected to replace brake pads that still contain asbestos, even though asbestos harms human health. Brake pads are manufactured using the cold press method, which has a composition is 60% epoxy resin, 35% filler, and 5% nylon fiber. The observed characteristics of the organic brake pad are mechanical, tribological, and thermal behavior using rubber seed shell and fruit shell fillers. This research conducted several results. Both friction coefficient values have met the performance values of the standard commercial brake pad material. The rubber seed shell has better wear resistance as filler in brake pad material than fruit shells. The type of wear for rubber seed shells is abrasive wear. The thermal analysis shows that the decomposition temperature of the rubber fruit shell is higher than the rubber seed shell.